2008
DOI: 10.1103/physrevlett.100.160405
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solution of Strongly Interacting Quasi-One-Dimensional Spinor Bose Gases

Abstract: We present an exact analytical solution of the fundamental system of quasi-one-dimensional spin-1 bosons with infinite delta repulsion. The eigenfunctions are constructed from the wave functions of noninteracting spinless fermions, based on Girardeau's Fermi-Bose mapping. We show that the spinor bosons behave like a compound of noninteracting spinless fermions and noninteracting distinguishable spins. This duality is especially reflected in the spin densities and the energy spectrum. We find that the momentum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
171
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(172 citation statements)
references
References 29 publications
(33 reference statements)
1
171
0
Order By: Relevance
“…Indeed, in the strongly interacting limit they have features in common with the TG gas. For example, in certain interacting limits, their ground-state wave function can be obtained analytically and it is similar to a TG gas for both components [24,25]. The intra-and interspecies interactions, which describe all the interaction processes in these mixtures, can be controlled experimentally by means of Feshbach and confinement induced resonances [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the strongly interacting limit they have features in common with the TG gas. For example, in certain interacting limits, their ground-state wave function can be obtained analytically and it is similar to a TG gas for both components [24,25]. The intra-and interspecies interactions, which describe all the interaction processes in these mixtures, can be controlled experimentally by means of Feshbach and confinement induced resonances [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…tinguishable spin-1/2 since any spin-spin exchange vanishes [36,41,46]. In both 1CBG and 2CBG, the local density-density correlation function then naturally vanishes since there is no double-space occupancy.…”
Section: Tonks-girardeau Regimementioning
confidence: 99%
“…Furthermore, recent studies of the ferromagnetic ground state revealed different dispersions for the charge and pseudospin excitations, which therefore exhibit a spin-charge separation [39,40]. The regime of strong interaction is still not completely understood, and even if Girardeau's Fermi-Bose mapping has been shown and used for the study of the one-dimensional (1D) spinor Bose gases [41] leading to a paramagnetic Tonk-Girardeau regime [36], this approach fails to provide first correction terms to this fermionization regime since the discernability of the bosons is missing.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of totally indistinguishable bosons and fermions, these phase relations lift the degeneracy completely (i.e. the famous Bose-Fermi mapping of Girardeau [48]), otherwise it is more complicated for more than two particles [42,43,49,50].…”
Section: B Kinematic Symmetriesmentioning
confidence: 99%
“…The eigensolutions at the unitary limit H τ ∞ can be algebraically constructed from the eigensolutions of H τ 0 by restricting the particle permutation antisymmetric states (19b) to the domains X I and X II , also called the 'snippet' basis [42,43,49,50,61]:…”
Section: Fig 5 Potential Energy Of Hamiltonianmentioning
confidence: 99%